Living standards, inequality, and consumption (1500–1800) - Nicolini, Esteban (2024)
Between 1500 and 1800, Iberian society was characterized by high inequality of income and wealth, low real wages that stimulated working relatively long hours and days, and some expansion consumption focused on low-quality manufactures. Despite the high levels of wealth of the upper groups living in large urban centers such as Madrid, Lisbon or Seville, Iberian consumption patterns did not experience a consumption revolution as they were highly conditioned by relatively low living standards. Although the second half of the eighteenth century was a turning point in Portugal and Spain – due to a reduction in the price of manufactured goods and greater openness to cultural foreign influences – economic and social changes excluded many disadvantaged groups of low-income earners, women, young children and poor people.